Sifat Fisis dan Mekanis Kayu Karet(Hevea brasiliensis MUELL Arg) Bekas Sadapan dan Kayu Karet tanpa Sadapan - Rudy Hartono Sipahutar; Tito Sucipto; Apri Heri Iswanto (Peronema Forestry Science Journal, 2015)
Rubber wood asone of light conctruction material was produced from community forest.  The objective of theseresearch was to evaluatethe physical and mechanical properties of tapping and untapping rubber wood for considering as construction materials.physical and mechanical testing refers to british standard (BS:373-1957). The result of these research showed that physical properties value such as air dry moisture content, specivic gravity, and longitudinal, radial, tangential shrinkage were 13,46-22,43%, 0,61-0,73,0,62-1,32%, 1,05-3,65% and 2,39-5,30%respectively for tapping rubber wood.  Furthermore forthe similar patameter, untapping rubber wood were 7,44-14,68%, 0,57-0,71 and 0,6-2,09%, 1,27-4,13%, 2,5-5,35% respectively.The mechanical properties value included of moe,mor, parallel compression strength, and hardness for tapping and untapping rubber wood were 67813-129480 kg/cm2 and52759-107817 kg/cm2, 751,61-1071,68 kg/cm2 and 649-899,74  kg/cm2, 83,79-148,43 kg/cm2 and 80,54-137,88  kg/cm2, 16,99-21,94 kg/cm2 and 12,7-17,9 kg/cm2 respectively.Key words: rubber wood, tapping and untapping, physical and mechanical properties